2004
DOI: 10.1212/01.wnl.0000129909.77753.c4
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal stroke in term infants with neonatal encephalopathy

Abstract: In a prospective cohort of 124 encephalopathic term infants, six infants had an acute focal stroke. All six encephalopathic patients with strokes presented with seizures. Neurodevelopmental outcome at 30 months was abnormal in all six patients and significantly worse when compared with the entire cohort overall. These findings suggest that in newborns with encephalopathy, acute focal strokes are an uncommon but serious occurrence with substantial risk for abnormal neurodevelopmental outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(63 citation statements)
references
References 14 publications
2
61
0
Order By: Relevance
“…40 On the basis of the mechanisms that can lead to arterial occlusion and known perinatal risk factors, the arterial occlusion in our patients could have taken place during 3 periods: 1) in later labor, 2) the intrapartum period, and 3) shortly after delivery, each period reflecting different risks factors. 13,20,41,42 In this study, we could not differentiate these periods. All infants underwent labor, none being born by prelabor cesarean Graph shows DWIs of a patient with an infarction within the PCA territory, showing severe HSI on day 3 (A) and mild-to-moderate HSI on day 10 (B).…”
Section: Figmentioning
confidence: 78%
See 1 more Smart Citation
“…40 On the basis of the mechanisms that can lead to arterial occlusion and known perinatal risk factors, the arterial occlusion in our patients could have taken place during 3 periods: 1) in later labor, 2) the intrapartum period, and 3) shortly after delivery, each period reflecting different risks factors. 13,20,41,42 In this study, we could not differentiate these periods. All infants underwent labor, none being born by prelabor cesarean Graph shows DWIs of a patient with an infarction within the PCA territory, showing severe HSI on day 3 (A) and mild-to-moderate HSI on day 10 (B).…”
Section: Figmentioning
confidence: 78%
“…10,11 PAIS is occasionally associated with hypoxic-ischemic encephalopathy (HIE). 12,13 The timing of presentation is often Ͼ2 hours after birth and may be up to 3-4 days.…”
mentioning
confidence: 99%
“…1,2,25,26 It is worthy of note that the focal character distinguishes PAIS from hypoxic-ischemic encephalopathy, although these 2 pathological conditions share many risk factors and can coexist in the same patient. 26 Cord abnormalities (mainly tight umbilical cord) were associated with a nonsignificant increase in the likelihood of PAIS in this study. Lee et al 2 also reported a significant difference between PAIS and control subjects for cord abnormalities (22% versus 6%).…”
Section: Discussionmentioning
confidence: 99%
“…15 Perinatal arterial ischemic stroke has been reported to coincide with hypoxic-ischemic encephalopathy; hypoxic-ischemic encephalopathy has been suggested to be a risk factor for perinatal stroke. 16 Birth asphyxia can lead to congestion, endothelial injury, and intravascular coagulation, thus leading to stroke. 17 Hypoxic-ischemic encephalopathy is more often present in full-term infants than in preterm infants with stroke.…”
Section: August 2013mentioning
confidence: 99%